KOMPETENSI MOTORIK KASAR BERBASIS GERAK FUNDAMENTAL SEBAGAI FONDASI PHYSICAL LITERACY ANAK USIA DINI - Imron Nugroho Saputro; Akmad Azlan Khoirurrozikin; Prayogi Dwina Angga; Muhammad Thoriq Hadad Akbar; Amanda Eka Rismawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of fundamental motor skills in early childhood is a crucial issue in the global discourse on physical literacy, as it serves as the foundation for long-term participation in physical activity. The limited empirical data from internationally standardized assessments in the Indonesian elementary school context necessitate a comprehensive mapping of motor development. This study aims to describe the profile of fundamental motor skills as the foundation for physical literacy in six-year-old children in six elementary schools within one urban village. A quantitative descriptive approach was used, involving 150 students who were assessed using the Test of Gross Motor Development–Second Edition (TGMD-2) to evaluate locomotor and manipulative skills. The results showed that the majority of children were in the good motor development category, with a predominance of locomotor skills and varying performance in manipulative skills. These findings confirm that the foundation of physical competence has been established since the beginning of elementary school and provide an empirical basis for developing an assessment-based physical education curriculum to support the ongoing development of physical literacy.